Influence of varying energy and protein levels on the performance and feed cost of broiler chickens (2015)
The influence of varying energy and protein levels on performance, carcass evaluation and gut morphology of broiler chickens were investigated in a 56-day feeding trial. A total of 192 one-day old Arbor acre broiler chickens were fed 6 diets at the starter and finisher phases. The diets were Recommended Energy-Recommended Protein (RERP, control), Recommended Energy-Lower Protein (RELP), Lower Energy-Recommended Protein (LERP), Lower Energy-Lower Protein (LELP), Higher Energy-Recommended Protein (HERP) and Higher Energy-Lower Protein (HELP). Birds were fed ad-libitum for 8 weeks and weighed weekly to determine their performance. Final body weight, average body weight gain and feed intake were recorded while the feed conversion ratios were determined. Feed cost in Naira (N) per kilogramme/diet for the six diets were determined. No significant (P>0.05) differences were recorded in the final body weight, average body weight gain and feed intake. Although, HERP and HELP diets enhanced these parameters. Feed conversion ratio were significantly (P<0.05) lowest in birds fed HERP and HELP diets. Birds on these treatments utilized their feed efficiently. Feed cost were significantly (P<0.05) influenced by varying energy and protein in diets. Feed cost increased with increased energy level. Diets with LELP had the least feed cost. In conclusion, feeding broilers with HERP and/or HELP gave better performance with an increased feed cost. However, lowering energy and protein in broiler diets will reduce feed cost at the expense of the bird's performance.